Laminated glass and vehicle
By using non-metal reflective films in laminated glass, the problems of large-area glass thermal insulation and electromagnetic shielding are solved, and the combination of efficient thermal insulation and excellent communication quality is achieved, reducing production costs and chromatic difference risks.
Patent Information
- Application Number
- CN202411347140.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-26
AI Technical Summary
Large areas of vehicle glass lead to thermal insulation problems. Traditional metal-coated reflective films will affect the electromagnetic environment of the antenna, resulting in signal attenuation and reduced communication quality.
Non-metal reflective films, including alternately stacked high-refractive index layers and low-refractive index layers, combined with polymer films and color adjustment layers, are used in laminated glass, replacing traditional metal coatings, improving thermal insulation properties and reducing electromagnetic environments The impact of
It effectively solves the heat insulation problem, avoids shielding of antenna signals, improves wireless communication quality, reduces production costs and color difference problems, and improves the appearance of the vehicle.
Smart Images

Figure CN119239077A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of vehicle glass, and in particular to a laminated glass and a vehicle. Background Art
[0002] With the rise of new energy vehicles, car design not only pursues innovation and fashion, but also emphasizes energy efficiency and environmental protection. Low drag coefficient is the key to achieving this goal, because it can significantly reduce air resistance during driving, thereby reducing energy consumption and extending the driving range of electric vehicles. In order to meet the demand for low wind resistance, many automakers have begun to adopt large-size panoramic front windshields, sunroofs and rear windshields. These designs not only enhance the appearance of the vehicle, but also provide passengers with a wider field of vision. However, as the glass coverage area of the vehicle increases, the problem of heat insulation becomes particularly prominent. Large areas of glass easily absorb solar radiation, causing the temperature inside the car to rise, which not only affects the comfort of passengers, but also increases the energy consumption of the air-conditioning system, offsetting the energy efficiency advantages brought by the low wind resistance design. Therefore, heat insulation has become an important consideration in the thermal management of the whole vehicle.
[0003] In order to solve the problem of heat insulation, most car manufacturers use the high reflectivity of metal coatings to block infrared and ultraviolet rays in solar radiation, thereby effectively reducing the accumulation of heat in the car. For example, a metal coating or alloy layer is directly deposited on a glass surface of laminated glass to obtain metal-coated glass, or a metal coating is deposited on a PET film to obtain metal-coated PET, which is then used in laminated glass.
[0004] However, although the above-mentioned use of metal coating reflection can play a role in heat insulation, it is found that the laminated glass containing metal coating will affect the electromagnetic environment around the antenna during use, and may have a certain shielding effect on the electromagnetic wave signal emitted by the antenna, resulting in signal attenuation, reducing the sensitivity and coverage of the antenna, and affecting the wireless communication quality inside the vehicle. Summary of the invention
[0005] Based on this, the first aspect of the present application provides a laminated glass, and its technical solution is as follows:
[0006] The laminated glass provided in the present application comprises a laminated outer glass plate, an inner glass plate, an adhesive layer and a non-metallic reflective film, wherein the outer glass plate has a first surface and a second surface, the inner glass plate has a third surface and a fourth surface, the adhesive layer is located between the second surface and the third surface, and the non-metallic reflective film is located between the second surface and the adhesive layer, or between the adhesive layer and the third surface, or on the fourth surface, or within the adhesive layer;
[0007] The direct solar reflectivity RE of the laminated glass measured from the first surface side satisfies: RE≥12%.
[0008] The non-metallic reflective film includes alternately stacked high refractive index layers and low refractive index layers, the refractive index of the high refractive index layer is denoted as n1, the refractive index of the low refractive index layer is denoted as n2, and n1 and n2 satisfy: n1-n2≥0.05.
[0009] Wherein, the non-metallic reflective film further comprises a polymer film, and the high refractive index layers and the low refractive index layers are alternately stacked on at least one surface of the polymer film.
[0010] Wherein, the non-metallic reflective film also includes a color adjustment layer, which is in direct contact only with the high refractive index layer in the non-metallic reflective film, or is in direct contact only with the low refractive index layer in the non-metallic reflective film, or is located between adjacent high refractive index layers and low refractive index layers.
[0011] Wherein, the thickness of the color adjustment layer is 0.1 μm-15 μm, or 1 μm-10 μm.
[0012] Wherein, the thickness of the non-metallic reflective film is 40 μm~200 μm.
[0013] Wherein, the materials of the high refractive index layer and the low refractive index layer are both inorganic compounds, and the total number of layers of the high refractive index layer and the low refractive index layer is 4 to 20 layers.
[0014] Wherein, the laminated glass includes at least one of the following features:
[0015] (1) The material of the high refractive index layer is oxide, nitride or oxynitride, and n1 satisfies: n1 ≥ 2.0;
[0016] (2) The material of the low refractive index layer is an oxide or a fluoride, and n2 satisfies: n2≤1.8;
[0017] (3) n1-n2 ≥ 0.2, or n1-n2 ≥ 0.5, or n1-n2 ≥ 0.8, or n1-n2 ≥ 1.0;
[0018] (4) The material of the high refractive index layer is an oxide, nitride, or oxynitride of at least one element selected from Zn, Ti, Si, Al, Sn, Se, Zr, Ni, In, Cr, W, Ca, Y, Nb, Cu, and Sm;
[0019] (5) The material of the low refractive index layer is selected from oxides or fluorides of at least one element selected from Si, Al and Mg.
[0020] Wherein, the materials of the high refractive index layer and the low refractive index layer are both organic polymers, the total number of layers of the high refractive index layer and the low refractive index layer is 50 to 5000 layers, and the organic polymer is selected from at least one of polyethylene, polypropylene, polylactic acid, poly(4-methyl-1-pentene), polyvinylidene fluoride, cyclic polyolefin, polymethyl methacrylate, polyvinyl chloride, polyvinyl alcohol, polyamide, polystyrene, polycarbonate, polyethylene terephthalate, polyethylene naphthalate, polyphenylene sulfide and polyetherimide; n1-n2≤0.15, or n1-n2≤0.1.
[0021] The laminated glass has a reflectivity of at least 75% for near infrared light with a wavelength of 900 nm to 1100 nm incident from the first surface side.
[0022] Wherein, within the frequency range of 30 MHz-3000 MHz, the absolute value of the difference between the maximum signal attenuation and the minimum signal attenuation of the laminated glass is ≤10 dB.
[0023] Among them, the visible light transmittance of the non-metallic reflective film is greater than or equal to 85%, or the visible light transmittance of the non-metallic reflective film is greater than 75% and less than or equal to 80%, or the visible light transmittance of the non-metallic reflective film is less than or equal to 60%.
[0024] Among them, the visible light transmittance of the laminated glass is greater than or equal to 70%, the total solar energy transmittance of the laminated glass is less than or equal to 60%, the RE is ≥ 20%, and the visible light reflectivity of the laminated glass measured from the first surface side is less than or equal to 15%.
[0025] Wherein, the visible light transmittance of the laminated glass is less than or equal to 10%, and the total solar energy transmittance of the laminated glass is less than or equal to 30%.
[0026] Wherein, the visible light transmittance of the laminated glass is greater than or equal to 70%, the total solar energy transmittance of the laminated glass is less than or equal to 55%, and the RE is ≥20%.
[0027] The shrinkage rate of the non-metallic reflective film in the machine direction MD is 2% to 4.5%, and the shrinkage rate of the non-metallic reflective film in the transverse direction TD is 1.1% to 4%.
[0028] Wherein, the minimum distance between the contour boundary of the non-metallic reflective film and the contour boundary of the laminated glass is 5 mm to 20 mm.
[0029] Among them, when measuring the outer surface reflection color Lab value of the laminated glass from the first surface side, the a value satisfies -2 to 0, and the b value satisfies -2 to 0.5; or, the a value satisfies -1 to 0, and the b value satisfies -1 to 0.5; or, the a value satisfies -0.5 to 0, and the b value satisfies -0.5 to 0.5.
[0030] A second aspect of the present application provides a vehicle, which includes the laminated glass as described above.
[0031] Compared with the traditional solution, this application has the following beneficial effects:
[0032] The present application adds a non-metallic reflective film to the laminated glass, which can directly replace the traditional metal coating. It can not only reflect infrared rays, but also solve the problem of heat insulation in the thermal management of the whole vehicle. At the same time, compared with the metal coating, the dielectric constant of the laminated glass after adding the non-metallic reflective film is closer to the surrounding air, which can avoid the impact on the electromagnetic environment around the antenna, and basically does not shield the electromagnetic wave signal emitted by the antenna. The signal has high transmittance, which is conducive to ensuring the quality of wireless communication inside the vehicle. At the same time, compared with the deposition of metal coatings, which is easily affected by process debugging and causes color difference problems, the non-metallic reflective film is less affected by process debugging, which can avoid color difference problems and is conducive to the overall appearance and aesthetics of the vehicle. In addition, the production cost of the non-metallic reflective film is lower than the deposition cost of the metal coating, which is conducive to reducing product costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions in the embodiments of the present application and to more completely understand the present application and its beneficial effects, the following is a brief introduction to the drawings required for the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.
[0034] Figure 1 A schematic structural diagram of a first embodiment of the laminated glass provided in the present application;
[0035] Figure 2 A schematic structural diagram of a second embodiment of the laminated glass provided in the present application;
[0036] Figure 3 A schematic structural diagram of a third embodiment of the laminated glass provided in the present application;
[0037] Figure 4 A schematic structural diagram of a fourth embodiment of the laminated glass provided in the present application;
[0038] Figure 5 A schematic structural diagram of a first embodiment of the non-metallic reflective film provided in the present application;
[0039] Figure 6 A schematic structural diagram of a second embodiment of the non-metallic reflective film provided in the present application;
[0040] Figure 7 This is a schematic top view of the laminated glass provided in this application. DETAILED DESCRIPTION
[0041] The present application will be further described in detail below in conjunction with specific embodiments. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present application more thoroughly understood.
[0042] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0043] the term
[0044] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:
[0045] In the present application, "plurality", "multiple", "multiple times", "plurality", etc., unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "one or more" means one or greater than or equal to two.
[0046] In this application, the terms "first", "second", "third", "fourth", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", "fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0047] The first aspect of the present application provides a laminated glass. Figure 1 In the first embodiment, the laminated glass 01 includes a laminated outer glass plate 11, an inner glass plate 12, an adhesive layer 13 and a non-metallic reflective film 14, wherein the outer glass plate 11 has a first surface 11A and a second surface 11B, the inner glass plate 12 has a third surface 12A and a fourth surface 12B, the adhesive layer 13 is located between the second surface 11B and the third surface 12A, and the non-metallic reflective film 14 is located between the second surface 11B and the adhesive layer 13.
[0048] See also Figure 2In the second embodiment, the laminated glass 02 includes a laminated outer glass plate 21, an inner glass plate 22, an adhesive layer 23 and a non-metallic reflective film 24, wherein the outer glass plate 21 has a first surface 21A and a second surface 21B, the inner glass plate 22 has a third surface 22A and a fourth surface 22B, the adhesive layer 23 is located between the second surface 21B and the third surface 22A, and the non-metallic reflective film 24 is located between the adhesive layer 23 and the third surface 22A.
[0049] See also Figure 3 In the third embodiment, the laminated glass 03 includes a laminated outer glass plate 31, an inner glass plate 32, an adhesive layer 33 and a non-metallic reflective film 34, the outer glass plate 31 has a first surface 31A and a second surface 31B, the inner glass plate 32 has a third surface 32A and a fourth surface 32B, the adhesive layer 33 is located between the second surface 31B and the third surface 32A, and the non-metallic reflective film 34 is located on the fourth surface 32B.
[0050] See also Figure 4 In the fourth embodiment, the laminated glass 04 includes a laminated outer glass plate 41, an inner glass plate 42, an adhesive layer 43, and a non-metallic reflective film 44. The outer glass plate 41 has a first surface 41A and a second surface 41B, the inner glass plate 42 has a third surface 42A and a fourth surface 42B, the adhesive layer 43 is located between the second surface 41B and the third surface 42A, the adhesive layer 43 includes a laminated first adhesive layer 431 and a second adhesive layer 432, and the non-metallic reflective film 44 is located between the first adhesive layer 431 and the second adhesive layer 432. In other embodiments, the non-metallic reflective film may also be located within the adhesive layer in other structures.
[0051] In the above embodiment, the first surface is the outer surface of the laminated glass facing the outside of the vehicle, and the fourth surface is the inner surface of the laminated glass facing the inside of the vehicle. The direct solar reflectance RE of the laminated glass measured from the first surface side satisfies: RE ≥ 12%. The above embodiments all add a non-metallic reflective film to the laminated glass, which can reflect infrared rays and solve the problem of heat insulation in the thermal management of the whole vehicle. Further optionally, the direct solar reflectance RE of the laminated glass measured from the first surface side satisfies: RE ≥ 20%. Further optionally, the direct solar reflectance RE of the laminated glass measured from the first surface side satisfies: RE ≥ 45%. The higher the direct solar reflectance RE, the better the heat insulation performance of the laminated glass.
[0052] In some embodiments, the laminated glass has a reflectivity of at least 75% for near infrared rays with a wavelength of 900nm to 1100nm incident from one side of the first surface. Further, the laminated glass has a reflectivity of at least 80% for near infrared rays with a wavelength of 900nm to 1100nm incident from one side of the first surface. Further, the laminated glass has a reflectivity of at least 85% for near infrared rays with a wavelength of 900nm to 1100nm incident from one side of the first surface. Even more, the laminated glass has a reflectivity of at least 90% for near infrared rays with a wavelength of 900nm to 1100nm incident from one side of the first surface. Since human skin is more sensitive to heat in the band near 1000nm, the laminated glass provided in the present application can not only have good heat insulation performance, but also further provide better human body surface comfort to passengers inside the vehicle.
[0053] If a metal coating is added to the traditional laminated glass, its dielectric constant is different from the dielectric constant of the surrounding air, and the metal has specific electromagnetic properties, which will affect the electromagnetic environment around the antenna, and then have a certain shielding effect on the electromagnetic wave signal emitted by the antenna, resulting in signal attenuation, thereby affecting the antenna's transceiver efficiency, reducing the antenna's sensitivity and coverage, and affecting the quality of wireless communication inside the vehicle. Compared with the traditional metal coating, adding a non-metallic reflective film to the laminated glass can avoid the impact on the electromagnetic environment around the antenna, and basically does not shield the electromagnetic wave signal emitted by the antenna, ensuring that 5G signals, WiFi signals, Bluetooth signals, GPS signals, ETC signals, and universal garage door opener signals have high transmittance, and reducing the attenuation of the laminated glass to the communication signal as much as possible. Optionally, within the frequency range of 30MHz-3000MHz, the absolute value of the difference between the maximum signal attenuation and the minimum signal attenuation of the laminated glass is ≤10dB, thereby maintaining the consistency of the full-band signal passing within the frequency range of 30MHz-3000MHz. Further optionally, within the frequency range of 30MHz-3000MHz, the absolute value of the difference between the maximum signal attenuation and the minimum signal attenuation of the laminated glass is ≤8dB. Further optionally, within the frequency range of 30MHz-3000MHz, the absolute value of the difference between the maximum signal attenuation and the minimum signal attenuation of the laminated glass is ≤5dB.
[0054] In addition, the deposited metal coating also has color difference problems due to production process debugging and other issues. In the prior art, laminated glass after depositing metal coating is usually blue or blue-green, and the color cast problem can be clearly seen. Compared with the deposited metal coating, the non-metallic reflective film is less affected by process debugging, which can avoid color difference problems and is beneficial to the overall appearance and aesthetics of the vehicle.
[0055] In addition, the deposition process of metal coating is relatively complicated and requires special equipment and materials, so the production cost is relatively high. Compared with deposited metal coating, non-metallic reflective film does not contain metal elements, such as Ag, Au, Cu, Al, Fe, Ni, Cr, Co, Mn and other metal elements, and its production cost is relatively low, which is conducive to reducing the overall cost of automobiles.
[0056] In summary, adding a non-metallic reflective film to the laminated glass can not only reflect infrared rays and solve the insulation problem of the thermal management of the whole vehicle, but also, compared with the metal coating, the dielectric constant of the laminated glass with the non-metallic reflective film is closer to the surrounding air, which can avoid the impact on the electromagnetic environment around the antenna, and basically does not shield the electromagnetic wave signal emitted by the antenna. The signal has high transmittance, which is conducive to ensuring the quality of wireless communication inside the vehicle. At the same time, compared with the deposition of metal coatings, which are easily affected by process debugging and cause color difference problems, the non-metallic reflective film is less affected by process debugging, which can avoid color difference problems and is conducive to the overall appearance and aesthetics of the vehicle. In addition, the deposition cost of the non-metallic reflective film is lower than that of the metal coating, which is conducive to reducing production costs.
[0057] Optionally, the thickness of the non-metallic reflective film is 40 μm to 200 μm. For example, the thickness of the non-metallic reflective film is 40 μm, 50 μm, 80 μm, 100 μm, 120 μm, 150 μm, 180 μm, or 200 μm. Further optionally, the thickness of the non-metallic reflective film is 50 μm to 100 μm.
[0058] See also Figure 5 and Figure 6 The non-metallic reflective film includes alternately stacked high refractive index layers 401 and low refractive index layers 402, the refractive index of the high refractive index layer 401 is recorded as n1, the refractive index of the low refractive index layer 402 is recorded as n2, and n1 and n2 satisfy: n1-n2≥0.05. Further optionally, n1 and n2 satisfy: n1-n2≥0.2. Further optionally, n1 and n2 satisfy: n1-n2≥0.5. Further optionally, n1 and n2 satisfy: n1-n2≥0.8.
[0059] Optionally, the non-metallic reflective film further comprises a polymer film 400, and the high refractive index layers 401 and the low refractive index layers 402 are alternately stacked on at least one surface of the polymer film 400. The polymer film 400 can be used to support the high refractive index layers 401 and the low refractive index layers 402. Optionally, the material of the polymer film 400 is selected from polyethylene terephthalate (PET), polyimide (PI), biaxially oriented polypropylene film (BOPP), etc.
[0060] Laminated glass can be used as front windshields, skylights, car windows, etc. When it rains, raindrops will adhere to the surface of the laminated glass. The shapes and sizes of these raindrops are irregular, but they all act as tiny lenses. When light passes through these raindrops, it will be further refracted and scattered, causing the path of the light to change. When traditional laminated glass with a metal coating is attached to water droplets on its first surface, the color of the reflected light usually becomes more complex and colorful, forming a colorful visual effect. And the observed color may also vary depending on the position and angle of the observer.
[0061] In order to avoid the above-mentioned complex and colorful colors observed by raindrops on the laminated glass, the non-metallic reflective film may further include a color adjustment layer 403, which can absorb specific colors in visible light, so that the color reflected by the outer surface of the laminated glass is a specific color, such as neutral gray, making the reflected color more uniform and reducing the generation of colorful colors caused by raindrops.
[0062] In the application, the color adjustment layer 403 can be formed by a magnetron sputtering process, a sol-gel process or a co-extrusion process. In some embodiments, the materials of the high refractive index layer and the low refractive index layer are both inorganic compounds, and the color adjustment layer 403 can be formed by a magnetron sputtering process or a sol-gel process. In other embodiments, the materials of the high refractive index layer and the low refractive index layer are both organic polymers, and the color adjustment layer 403 can be formed by a magnetron sputtering process, a sol-gel process or a co-extrusion process.
[0063] Specifically, the color adjustment layer 403 can absorb a specific color in the visible light. For example, the color adjustment layer 403 can absorb red light with a wavelength in the range of 620nm to 750nm, and the color adjustment layer 403 contains a red light absorber, and the red light absorber can be, for example, a dye-based red light absorber or a pigment-based red light absorber; for another example, the color adjustment layer 403 can absorb blue light with a wavelength in the range of 420nm to 480nm, and the color adjustment layer 403 contains a blue light absorber. The blue light absorber can be exemplified by an azo blue light absorber, an isoindolinone blue light absorber, a quinophthalone blue light absorber, a benzimidazolone blue light absorber or an organic-inorganic composite blue light absorber; for example, the color adjustment layer 403 can absorb yellow light with a wavelength in the range of 570nm to 590nm, and the color adjustment layer 403 contains a yellow light absorber, and the yellow light absorber can be exemplified by a metal coordination compound, an azo dye or a conjugated polycyclic organic compound containing heteroatoms.
[0064] exist Figure 5In the embodiment, the color adjustment layer 403 is a layer of the non-metallic reflective film that is farthest from the polymer film 400 , and the color adjustment layer 403 is in direct contact only with the low refractive index layer 402 of the non-metallic reflective film.
[0065] exist Figure 6 In the embodiment, the color adjustment layer 403 is a layer of the non-metallic reflective film that is closest to the polymer film 400 , and the color adjustment layer 403 is directly in contact with only the high refractive index layer 401 of the non-metallic reflective film.
[0066] In some other implementations, the color adjustment layer 403 may also be located between adjacent high refractive index layers 401 and low refractive index layers 402 .
[0067] Optionally, the color adjustment layer 403 is a layer of the non-metallic reflective film that is closest to the first surface.
[0068] Optionally, a layer of the non-metallic reflective film closest to the first surface is a high refractive index layer.
[0069] Optionally, a layer of the non-metallic reflective film closest to the first surface is a low refractive index layer.
[0070] Optionally, the color adjustment layer has a thickness of 1 μm to 10 μm. For example, the color adjustment layer has a thickness of 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, or 10 μm.
[0071] Optionally, the visible light transmittance TL1 of the non-metallic reflective film excluding the color adjustment layer satisfies: TL1 ≥ 85%. Further optionally, TL1 satisfies: TL1 ≥ 90%.
[0072] Optionally, the visible light transmittance TL2 of the non-metallic reflective film including the color adjustment layer satisfies: 75%<TL2≤80, and can be applied to laminated glass with higher visible light transmittance.
[0073] Optionally, the visible light transmittance TL2 of the non-metallic reflective film including the color adjustment layer satisfies: TL2≤60. Further optionally, TL2 satisfies: TL2≤55. The present invention can be applied to laminated glass with relatively low visible light transmittance.
[0074] In some embodiments, the laminated glass has a high visible light transmittance and can be used for front windshields, front door glass, rear windshields, etc., to meet high transmittance requirements and ensure driving safety. Optionally, the visible light transmittance of the laminated glass is greater than or equal to 70%. Optionally, the visible light transmittance of the laminated glass is 70% to 95%, and specific examples include 70%, 75%, 80%, 85%, 90%, 95%, etc.
[0075] In other embodiments, the laminated glass has a lower visible light transmittance and can be used for the sunroof glass, rear door glass, triangular glass, etc. of the vehicle to prevent rear passengers from feeling the glare of the sun. Optionally, the visible light transmittance of the laminated glass is less than or equal to 30%. Optionally, the visible light transmittance of the laminated glass is 0.5% to 30%, and specific examples include 0.5%, 1%, 2%, 3%, 4%, 5%, 8%, 10%, 15%, 20%, 25%, 30%, etc. Further optionally, the visible light transmittance of the laminated glass is less than or equal to 10%. Optionally, the visible light transmittance of the laminated glass is 0.5% to 10% to provide better heat insulation and privacy protection.
[0076] Optionally, the reflectivity RL of the laminated glass to visible light incident from one side of the first surface satisfies: RL≤20%, or RL≤18%, or RL≤15%, or RL≤12%, etc., or RL≤11%, so as to avoid light pollution to the environment outside the vehicle.
[0077] Optionally, the total solar transmittance TTS of the laminated glass satisfies: TTS≤60%, or TTS≤55%, or TTS≤50%, or TTS≤45%, or TTS≤40%, or TTS≤30%, so as to provide better heat insulation effect.
[0078] In some embodiments, the shrinkage rate of the non-metallic reflective film in the machine direction MD (Machine Direction) is 2% to 4.5%, and the shrinkage rate of the non-metallic reflective film in the transverse direction TD (Transverse Direction) is 1.1% to 4%, so that the non-metallic reflective film is not easy to curl during the process of making laminated glass and will not wrinkle after making laminated glass. Wherein, the machine direction MD represents the flow direction, and the transverse direction TD represents the direction orthogonal to the machine direction MD. The shrinkage rate is measured and calculated as follows: taking the size D1 at 25°C as the reference, the size when heated at 150°C for 15 minutes and then cooled to 25°C is D2, and the shrinkage rate = 100% * (D2-D1) / D1. The shrinkage rate calculated according to the size measured along the machine direction MD is the shrinkage rate of the machine direction MD, and the shrinkage rate calculated according to the size measured along the transverse direction TD is the shrinkage rate of the transverse direction TD. Optionally, the shrinkage rate of the non-metallic reflective film in the machine direction MD is 2.5% to 4%, and the shrinkage rate of the non-metallic reflective film in the transverse direction TD is 1.5% to 3.5%.
[0079] See also Figure 7The laminated glass has a contour boundary 500, and the non-metallic reflective film has a contour boundary 600. The contour boundary 500 of the laminated glass and the contour boundary 600 of the non-metallic reflective film are parallel to each other. The contour boundary 600 of the non-metallic reflective film is smaller than the contour boundary 500 of the laminated glass, that is, the contour boundary 600 of the non-metallic reflective film is inward compared to the contour boundary 500 of the laminated glass. The distance between the contour boundary 600 of the non-metallic reflective film and the contour boundary 500 of the laminated glass is T1, T2, T3, T4, the minimum value of T1, T2, T3, T4 is the minimum distance between the contour boundary 600 of the non-metallic reflective film and the contour boundary 500 of the laminated glass, the minimum distance is 5mm~20mm, specifically 5mm, 6mm, 8mm, 10mm, 12mm, 15mm, 18mm, 20mm, etc., so as to facilitate the non-metallic reflective film to be more stably sandwiched in the laminated glass and facilitate the trimming process in the process of manufacturing the laminated glass.
[0080] In some embodiments, the Lab value of the outer surface reflection color of the laminated glass is measured from the first surface side, and the a value satisfies -2 to 0, and the b value satisfies -2 to 0.5, so as to facilitate obtaining a laminated glass with a neutral and beautiful appearance. Optionally, the a value satisfies -1 to 0, and the b value satisfies -1 to 0.5. Further optionally, the a value satisfies -0.5 to 0, and the b value satisfies -0.5 to 0.5.
[0081] In the present application, the non-metallic reflective film includes alternately stacked high-refractive index layers and low-refractive index layers, and the materials of the high-refractive index layers and the low-refractive index layers are both non-metallic materials.
[0082] In some embodiments, the materials of the high refractive index layer and the low refractive index layer are both inorganic compounds, and the total number of layers of the high refractive index layer and the low refractive index layer is 4 to 20. Optionally, n1 and n2 satisfy: n1-n2≥0.2. Further optionally, n1 and n2 satisfy: n1-n2≥0.5. Further optionally, n1 and n2 satisfy: n1-n2≥0.8. Further optionally, n1 and n2 satisfy: n1-n2≥1.0.
[0083] Optionally, the material of the high refractive index layer is oxide, nitride or oxynitride, and n1 satisfies: n1≥2.0. Further optionally, n1 satisfies: n1≥2.1. Further optionally, n1 satisfies: n1≥2.2. Further optionally, n1 satisfies: n1≥2.3. Further optionally, n1 satisfies: n1≥2.4.
[0084] Optionally, the material of the high refractive index layer is selected from oxides, nitrides, or oxynitrides of at least one element selected from Zn, Ti, Si, Al, Sn, Se, Zr, Ni, In, Cr, W, Ca, Y, Nb, Cu, and Sm, for example, selected from at least one of TiO2, Nb2O5, Ta2O5, ZrO2, Si3N4, ZrN, and TiN.
[0085] Optionally, the material of the low refractive index layer is oxide or fluoride, and n2 satisfies: n2≤1.8. Further optionally, n2 satisfies: n2≤1.7. Further optionally, n2 satisfies: n2≤1.6. Further optionally, n2 satisfies: n2≤1.5.
[0086] Optionally, the material of the low refractive index layer is selected from oxides or fluorides of at least one element among Si, Al and Mg, for example, selected from at least one of SiO2 and Al2O3.
[0087] The high refractive index layer and the low refractive index layer can be formed by magnetron sputtering. When the non-metal reflective film includes a polymer film, the high refractive index layer and the low refractive index layer can be alternately deposited on the polymer film by magnetron sputtering.
[0088] In other embodiments, the materials of the high refractive index layer and the low refractive index layer are both organic polymers, and the total number of layers of the high refractive index layer and the low refractive index layer is 50 to 5000.
[0089] Optionally, n1 and n2 satisfy: 0.5≤n1-n2≤1.0. Further optionally, n1 and n2 satisfy: 0.8≤n1-n2≤1.0.
[0090] Optionally, the organic polymer is selected from at least one of polyethylene, polypropylene, polylactic acid, poly(4-methyl-1-pentene), polyvinylidene fluoride, cyclic polyolefin, polymethyl methacrylate, polyvinyl chloride, polyvinyl alcohol, polyamide, polystyrene, polycarbonate, polyethylene terephthalate, polyethylene naphthalate, polyphenylene sulfide and polyetherimide.
[0091] The high refractive index layer and the low refractive index layer can be formed by a co-extrusion process. When the non-metallic reflective film includes a polymer film, the polymer film can be formed by the co-extrusion process at the same time.
[0092] The outer glass plate includes a first surface and a second surface disposed opposite to each other. The outer glass plate is transparent glass or tinted glass, and the thickness of the outer glass plate is 0.7 mm to 4.0 mm, and specific examples include 0.7 mm, 1 mm, 1.6 mm, 2.1 mm, 3.2 mm, 4 mm, etc. Optionally, the thickness of the outer glass plate is 1.6 mm to 3.5 mm.
[0093] The inner glass plate includes a third surface and a fourth surface disposed opposite to each other. The inner glass plate is transparent glass or tinted glass, and the thickness of the inner glass plate is 0.7 mm to 4.0 mm, and specific examples include 0.7 mm, 1 mm, 1.6 mm, 2.1 mm, 3.2 mm, 4 mm, etc. Optionally, the thickness of the outer glass plate is 0.7 mm to 2.1 mm.
[0094] The adhesive layer is arranged between the second surface and the third surface, and connects the outer glass plate and the inner glass plate. It is understandable that the second surface of the outer glass plate is connected to the third surface of the inner glass plate by the adhesive layer. The present application does not specifically limit the material of the adhesive layer. Optionally, the material of the adhesive layer may include polyvinyl butyral (PVB), or ethylene-vinyl acetate copolymer (EVA), or ionic polymer film (SGP). When the adhesive layer includes a first adhesive layer and a second adhesive layer, the first adhesive layer and the second adhesive layer are each independently selected from at least one of polyvinyl butyral (PVB), ethylene-vinyl acetate copolymer (EVA) and ionic polymer film (SGP). The thickness of the adhesive layer is 0.38 mm to 2.28 mm. For example, the thickness of the adhesive layer may be, but is not limited to, 0.38 mm, or 0.76 mm, or 1.14 mm, or 1.52 mm, or 1.9 mm, or 2.28 mm, or other values between 0.38 mm and 2.28 mm.
[0095] The second aspect of the present application provides a vehicle, which includes the laminated glass as described above. The above vehicle has all the advantages of the above laminated glass, which will not be described in detail here.
[0096] The following is further described in conjunction with specific embodiments and comparative examples. The structures of the laminated glass in the following specific embodiments and comparative examples are as follows:
[0097] Comparative Example 1 and Examples 1-2
[0098] Comparative Example 1: 2.1mm thick transparent glass (outer glass plate) + 0.76mm thick transparent PVB (adhesive layer) + 2.1mm thick green glass (inner glass plate)
[0099] Example 1: 2.1 mm thick transparent glass (outer glass plate) + 0.38 mm thick transparent PVB (first bonding layer) + 0.05 mm thick non-metallic reflective film (without color adjustment layer) + 0.38 mm thick transparent PVB (second bonding layer) + 2.1 mm thick green glass (inner glass plate)
[0100] Example 2: 2.1mm thick transparent glass (outer glass plate) + 0.38mm thick transparent PVB (first bonding layer) + 0.05mm thick non-metallic reflective film (without color adjustment layer) + 0.38mm thick heat-absorbing PVB (second bonding layer) + 2.1mm thick green glass (inner glass plate)
[0101] The visible light transmittance TL, visible light reflectance RL, solar energy direct reflectance RE, and total solar energy transmittance TTS of the laminated glasses of Comparative Example 1 and Examples 1-2 were tested, and the measurement results were recorded in Table 1.
[0102] Visible light transmittance TL: measured and calculated according to standard ISO9050.
[0103] Visible light reflectance RL: measured and calculated from the first surface side of the laminated glass according to standard ISO9050.
[0104] Solar direct reflectivity RE: measured and calculated from the first surface side of the laminated glass according to standard ISO9050.
[0105] Total solar transmittance TTS: measured and calculated according to standard ISO9050.
[0106] Table 1: Measurement results of Comparative Example 1 and Examples 1-2
[0107]
[0108] It can be seen from Table 1 that Comparative Example 1 does not have the non-metallic reflective film described in the present application. After the non-metallic reflective film is added to Example 1 and Example 2, the visible light transmittance TL of Example 1 and Example 2 is slightly reduced, but still greater than 70%; the visible light reflectivity RL of Example 1 and Example 2 is slightly increased, but still less than 15%; the direct solar energy reflectivity RE of Example 1 and Example 2 is greatly increased to more than 20%, and the total solar energy transmittance TTS of Example 1 and Example 2 is greatly reduced to below 60%, and even to below 55%, so that the laminated glass of Example 1 and Example 2 has excellent heat insulation effect.
[0109] Comparative Example 2 and Examples 3-7
[0110] Comparative Example 2: 2.1mm thick transparent glass (outer glass plate) + 0.76mm thick transparent PVB (adhesive layer) + 2.1mm thick transparent glass (inner glass plate)
[0111] Example 3: 2.1mm thick transparent glass (outer glass plate) + 0.38mm thick transparent PVB (first bonding layer) + 0.054mm thick non-metallic reflective film (TL=58%, including color adjustment layer) + 0.76mm thick gray PVB (second bonding layer) + 2.1mm thick transparent glass (inner glass plate)
[0112] Example 4: 2.1mm thick transparent glass (outer glass plate) + 0.38mm thick transparent PVB (first bonding layer) + 0.054mm thick non-metallic reflective film (TL=58%, including color adjustment layer) + 0.76mm thick gray PVB (second bonding layer) + 2.1mm thick green glass (inner glass plate)
[0113] Example 5: 2.1mm thick transparent glass (outer glass plate) + 0.38mm thick transparent PVB + 0.054mm thick non-metallic reflective film (TL=80%, including color adjustment layer) + 0.38mm thick transparent PVB (second adhesive layer) + 2.1mm thick green glass (inner glass plate)
[0114] Example 6: 2.1mm thick transparent glass (outer glass plate) + 0.38mm thick transparent PVB + 0.054mm thick non-metallic reflective film (TL=80%, including color adjustment layer) + 0.76mm thick transparent heat-absorbing PVB (second adhesive layer) + 2.1mm thick transparent glass (inner glass plate)
[0115] Example 7: 2.1 mm thick transparent glass (outer glass plate) + 0.38 mm thick transparent PVB + 0.054 mm thick non-metallic reflective film (TL=80%, including color adjustment layer) + 0.38 mm thick transparent PVB (second adhesive layer) + 2.1 mm thick transparent glass (inner glass plate)
[0116] The visible light transmittance TL, solar direct reflectance RE, total solar transmittance TTS, and outer surface reflection color Lab value of the laminated glasses of Comparative Example 2 and Examples 3-7 were tested, and the measurement results were recorded in Table 2.
[0117] External surface reflected color Lab value: measured and calculated from the first surface side of the laminated glass based on CIE1976 Lab color space and D65 light source, the a value represents the red-green value of the visible light reflected color, and the b value represents the yellow-blue value of the visible light reflected color.
[0118] Table 2: Measurement results of Comparative Example 2 and Examples 3-7
[0119]
[0120] As shown in Table 2, comparative example 2 uses transparent glass and transparent PVB, so that its direct solar reflectance RE and total solar transmittance TTS do not meet the use requirements, but the a value and b value of the outer surface reflection color are both -0.5~0.5, which is very close to the neutral color.
[0121] Embodiment 3-4 adopts non-metallic reflective film and gray PVB, so that its visible light transmittance TL≤5%, or even TL≤2%, solar energy direct reflectance RE≥12%, and total solar energy transmittance TTS≤30%. It has excellent heat insulation effect and prevents sunlight glare, and can also play a role in privacy protection; at the same time, the a value of the outer surface reflection color satisfies -1.5~0, and the b value satisfies -1~0, with a relatively neutral and visually good reflection color appearance.
[0122] Examples 5-7 use non-metallic reflective film and transparent PVB to achieve visible light transmittance TL ≥ 70%, direct solar reflectance RE ≥ 20%, even RE ≥ 24%, even RE ≥ 30%, total solar transmittance TTS ≤ 55%, even TTS ≤ 50%, and have excellent heat insulation effect; at the same time, the a value of the reflected color on the outer surface satisfies -2~0, and the b value satisfies -2~0.5, even the a value satisfies -0.5~0, and the b value satisfies 0~0.5, and has a relatively neutral and visually good reflective color appearance.
[0123] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0124] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.
Claims
1. A laminated glass, characterized in that: The invention comprises a laminated outer glass plate, an inner glass plate, an adhesive layer and a non-metallic reflective film, wherein the outer glass plate has a first surface and a second surface, the inner glass plate has a third surface and a fourth surface, the adhesive layer is located between the second surface and the third surface, and the non-metallic reflective film is located between the second surface and the adhesive layer, or between the adhesive layer and the third surface, or on the fourth surface, or within the adhesive layer; The direct solar reflectivity RE of the laminated glass measured from the first surface side satisfies: RE≥12%.
2. The laminated glass according to claim 1, characterized in that: The non-metallic reflective film includes alternately stacked high refractive index layers and low refractive index layers, the refractive index of the high refractive index layer is denoted as n1, the refractive index of the low refractive index layer is denoted as n2, and n1 and n2 satisfy: n1-n2≥0.
05.
3. The laminated glass according to claim 2, characterized in that: The non-metallic reflective film further comprises a polymer film, and the high refractive index layers and the low refractive index layers are alternately stacked on at least one surface of the polymer film.
4. The laminated glass according to claim 2, characterized in that: The non-metallic reflective film further comprises a color adjustment layer, which is in direct contact only with the high refractive index layer in the non-metallic reflective film, or is in direct contact only with the low refractive index layer in the non-metallic reflective film, or is located between adjacent high refractive index layers and low refractive index layers.
5. The laminated glass according to claim 4, characterized in that: The thickness of the color adjustment layer is 0.1 μm to 15 μm, or 1 μm to 10 μm.
6. The laminated glass according to claim 1, characterized in that: The thickness of the non-metallic reflective film is 40 μm to 200 μm.
7. The laminated glass according to any one of claims 2 to 6, characterized in that: The materials of the high refractive index layer and the low refractive index layer are both inorganic compounds, and the total number of layers of the high refractive index layer and the low refractive index layer is 4 to 20.
8. The laminated glass according to claim 7, characterized in that: Includes at least one of the following features: (1) The material of the high refractive index layer is oxide, nitride or oxynitride, and n1 satisfies: n1 ≥ 2.0; (2) The material of the low refractive index layer is an oxide or a fluoride, and n2 satisfies: n2≤1.8; (3) n1-n2 ≥ 0.2, or n1-n2 ≥ 0.5, or n1-n2 ≥ 0.8, or n1-n2 ≥ 1.0; (4) The material of the high refractive index layer is an oxide, nitride, or oxynitride of at least one element selected from Zn, Ti, Si, Al, Sn, Se, Zr, Ni, In, Cr, W, Ca, Y, Nb, Cu, and Sm; (5) The material of the low refractive index layer is selected from oxides or fluorides of at least one element among Si, Al and Mg.
9. The laminated glass according to any one of claims 2 to 6, characterized in that: The materials of the high refractive index layer and the low refractive index layer are both organic polymers, the total number of layers of the high refractive index layer and the low refractive index layer is 50 to 5000 layers, and the organic polymer is selected from at least one of polyethylene, polypropylene, polylactic acid, poly(4-methyl-1-pentene), polyvinylidene fluoride, cyclic polyolefin, polymethyl methacrylate, polyvinyl chloride, polyvinyl alcohol, polyamide, polystyrene, polycarbonate, polyethylene terephthalate, polyethylene naphthalate, polyphenylene sulfide and polyetherimide; n1-n2≤0.15, or n1-n2≤0.
1.
10. The laminated glass according to claim 1, characterized in that: The laminated glass has a reflectivity of at least 75% with respect to near infrared light with a wavelength of 900 nm to 1100 nm incident from the first surface side.
11. The laminated glass according to claim 1, characterized in that: In the frequency range of 30 MHz to 3000 MHz, the absolute value of the difference between the maximum signal attenuation and the minimum signal attenuation of the laminated glass is ≤10 dB.
12. The laminated glass according to claim 1, characterized in that: The visible light transmittance of the non-metallic reflective film is greater than or equal to 85%, or the visible light transmittance of the non-metallic reflective film is greater than 75% and less than or equal to 80%, or the visible light transmittance of the non-metallic reflective film is less than or equal to 60%.
13. The laminated glass according to claim 1, characterized in that: The visible light transmittance of the laminated glass is greater than or equal to 70%, the total solar energy transmittance of the laminated glass is less than or equal to 60%, the RE is ≥ 20%, and the visible light reflectivity of the laminated glass measured from the first surface side is less than or equal to 15%.
14. The laminated glass according to claim 1, characterized in that: The visible light transmittance of the laminated glass is less than or equal to 10%, and the total solar energy transmittance of the laminated glass is less than or equal to 30%; or The visible light transmittance of the laminated glass is greater than or equal to 70%, the total solar energy transmittance of the laminated glass is less than or equal to 55%, and the RE is ≥ 20%.
15. The laminated glass according to claim 1, characterized in that: The shrinkage rate of the non-metallic reflective film in the machine direction MD is 2% to 4.5%, and the shrinkage rate of the non-metallic reflective film in the transverse direction TD is 1.1% to 4%.
16. The laminated glass according to claim 1, characterized in that: The minimum distance between the contour boundary of the non-metallic reflective film and the contour boundary of the laminated glass is 5 mm to 20 mm.
17. The laminated glass according to claim 1, characterized in that: The Lab value of the outer surface reflection color of the laminated glass is measured from the first surface side, and the a value satisfies -2 to 0, and the b value satisfies -2 to 0.5; or, the a value satisfies -1 to 0, and the b value satisfies -1 to 0.5; or, the a value satisfies -0.5 to 0, and the b value satisfies -0.5 to 0.
5.
18. A vehicle, characterized in that: The laminated glass comprises the laminated glass according to any one of claims 1 to 17.
Citation Information
Patent Citations
Laminated glass for vehicle window
CN101243023A
Low-emissivity coated glass and sandwich glass product thereof
CN103072341A
Heat-insulating laminated glass and manufacturing method thereof
CN112297543A
Automobile -used laminated glass
CN207944027U
Heat reflective sandwich glass
CN2820861Y
